Socio- economic and demographic variables and their relation to relative poverty A survey applied to a sample of Saudi families’ in Riyadh city - Al-Rashidi, Abdul Mohsen Ghazi (Journal of Humanities & Social Sciences, 2018)
The study aimed to define the social, economic and demographic characteristics of the relatively poor households in Riyadh, by identifying saving methods, spending measures, consumption patterns, and expenditure aspects of the relatively poor family, and then linking them with some social, economic and demographic variables such as career ranks, years of service- total family income- the educational level of the family head- type and ownership type of housing, and number of family members). Where some research questions were formulated and which help identifying the differences among the family in the sample of the study. Questionnaire was used as data collection tool. It included five main themes; the first theme included the primary data of the study sample. The second theme included identification of the dominant consumption patterns of the study sample. The third theme discussed the relative monthly spending pattern of the poor family in the study population. The fourth theme included the arrangements made by relatively poor families in the study population. Lastly; the fifth theme, identifies the culture of savings of the family in the study population. The study population was determined by Saudi employees at the public sector in a number of ministries in Riyadh. A random sample of 394 individuals was drawn. The study used the social survey method. A number of statistical methods were used to process the study data through the use of the program Statistical Package for the Social Sciences (SPSS). The study reached a number of findings: The general characteristics of the study sample were as follows: It was found that the entire study population are heads of households and are holding prominent positions –grade seven and below- , their educational qualification is undergraduate and below. About 60% of the study sample is less than 5 persons; while 39% are five or less than 10. 96% of the study sample lives as independent families away from their extended families. The only income source that the family depends upon – in the study sample- is the salary of the household head. The total monthly income of all the relatively poor families in the study sample SR 10723 and less, and that 58% of the study sample live in apartments and the rest of the study sample either live in floors or villas. 64% of study sample do not own accommodation, while only 35% own their own housing. The means of transportation used by most of the study sample is one car. 77% of the study sample use government hospitals for treatment. Entertainment means of the relatively poor families in the study sample is either general parks or children’s games in the house. 67% of the study sample has financial commitments towards the National Banks. The children of 66% of the study sample are studying at government schools, whereas only 5% of them study at private schools. The children of the remaining percentage did not reach the school age. The prevailing consumption pattern of the relatively poor families in the study community is the balanced consumption pattern, quite far away from the luxurious or the squandering consumption pattern. While the monthly expenses are low in all needs except for two of these basic needs, these are: Food and clothing. Spending arrangements of relatively poor families in the study community are good to some extent. Lastly, the culture of savings of relatively poor families was significantly low. The study came out with the following recommendations: Educating the relatively poor families about the importance of rationalizing consumption, reconsider priorities when spending so that there shall be more concentration on necessities and avoiding extravagance in consumption. The awareness and education shall be carried out by the various media organizations. The respective parties of media organizations and educational sectors should educate people by raising the level of savings culture within them by presenting awareness programs hosting experts in these fields. The respective parties shall adopt national approach through which suitable measurement shall be set and relative poverty line in the Kingdom of Saudi Arabia shall be outlined. Further studies about the conditions of relatively poor families in the Saudi society shall be carried out. It is preferable that these studies are carried out every three years because prices are not stable, they are continuously changing.